Cerebrospinal fluid lipocalin 2 as a novel biomarker for the differential diagnosis of vascular dementia - Llorens, Franc (2020)
The clinical diagnosis of vascular dementia (VaD) is based on imaging criteria, and specific biochemical markers are not available. Here, we investigated the potential of cerebrospinal fluid (CSF) lipocalin 2 (LCN2), a secreted glycoprotein that has been suggested as mediating neuronal damage in vascular brain injuries. The study included four independent cohorts with a total n = 472 samples. LCN2 was significantly elevated in VaD compared to controls, Alzheimer's disease (AD), other neurodegenerative dementias, and cognitively unimpaired patients with cerebrovascular disease. LCN2 discriminated VaD from AD without coexisting VaD with high accuracy. The main findings were consistent over all cohorts. Neuropathology disclosed a high percentage of macrophages linked to subacute infarcts, reactive astrocytes, and damaged blood vessels in multi-infarct dementia when compared to AD. We conclude that CSF LCN2 is a promising candidate biochemical marker in the differential diagnosis of VaD and neurodegenerative dementias.